Irrigation Canal Design In Tana Lia Irrigation Area In Tana Tidung District Narth Kalimantan Utara - MIR, A (KURVA S JURNAL MAHASISWA, 2013)
ABSTRACTTana lia is sub district in Tana Tidung District, North Kalimantan. There is potensial irrigation area ± 300 Hectare. The objective of this research is planning of developing irrigation and design of irrigation canal.Reveloping of irrigation tleeds irrigation canal design of primary, secondary and tersiary channels design of irrigation channel usad meteorology data : rainfall, temperature, humidity wind speed radiation, tophography, land use and soil prapertis.The result show that maximum water reed of irrigation is 1,692 lt/dt/ha. Dimensian trapezoid  primary irrigation canal SM 1 area L = 370 m, b = 0,90 m, T = 2,10 m, and h = 1,22 m. Dimensian of  trapezoid secondary irrigation channel SJ 1 area L = 450 m, b = 0,35 m, T = 0,75 m and h = 0,63 m. Dimensian of  trapezoid tersiary irrigation channel ST 11 area L = 335 m, b = 0,25 m, T = 0,55 m and h = 0,55 m.